Proses pembentukan feofotin daun suji sebagai bahan aktif photosensitizer akibat pemberian variasi suhu (The process of forming suji leaves feofotin as an active ingredient in the photosensitizer due to temperature variations) - Ari Arfandi; - Ratnawulan; Yenni Darvina (Department of Physics – Universitas Negeri Padang UNP, 2013)
ABSTRACTCancer is one kind of disease that has difficulties to treat, can be cured by using drugs which derived from natural materials in Indonesia. This treatment know a cancer treatment that uses three important factors such as the photosensitizer, oxygen and light, whereas this cancer therapy called photodynamic therapy (TFD). Photosensitizer which is required can be obtained from the suji leaves (Pleomele angusti-folia NE Brown) that were heated. The purpose of this researchs determined the content amount of chlorophyll content that suji leaves before it was heated, and knew the maximum temperature required to produce feofitin with maximum absorbance value moreover, determined purpose of this research the correlation feofitin absorbance value and the number of chlorophyll content in suji leaves after heating process. Base heating process on the research conducted, the amount of chlorophyll content which in suji leaves have heating process is 11,26453 μg / ml, in addition the maximum absorbance value feofitin on process at 900C with a maximum absorbance value is 1,90130 μg / ml. moreover a correlation between the total value absorbance with the amount of content chlorophyll in the suji leaves, however the relationship is not continuous. Keywords: suji leaves, feofitin, photosensitizer